Tracing stars in Milky Way satellites with a-sloth. Issue 1 (9th April 2022) - Chen, Li-Hsin; Magg, Mattis; Hartwig, Tilman; Glover, Simon C O; Ji, Alexander P; Klessen, Ralf S
ABSTRACT: We study the stellar mass-to-halo mass (SMHM) relation at z = 0 in 30 Milky Way (MW)-like systems down to the ultrafaint ($M_{\rm *}\lt 10^5\, {\rm M}_\odot$ ) regime using the semi-analytic model a-sloth . A new model allows us to follow star formation (SF) and the stochastic stellar feedback from individually sampled Pop II stars. Our fiducial model produces consistent results with the SMHM relation derived from abundance matching and the observed cumulative stellar mass function above the observational completeness. We find a plateau in the SMHM relation in the ultrafaint regime. The stellar mass of this plateau tells us how many stars formed before supernovae occur and regulate further SF, which is determined by the Pop II SF efficiency. We also find that the number of luminous satellites increases rapidly as M * decreases until $M_{\rm *}≈ 10^4\, {\rm M}_\odot$ . Finally, we find that the relative streaming velocity between baryons and dark matter at a high redshift is important in determining the number of ultrafaint dwarf galaxies at z = 0. The new model in a-sloth provides a framework to study the stellar properties and the formation history of metal-poor stars in MW and its satellites.